Olive Germplasm - The Olive Cultivation, Table Olive and Olive Oil Industry in Italy 2012
DOI: 10.5772/52141
|View full text |Cite
|
Sign up to set email alerts
|

Technological Aspects of Olive Oil Production

Abstract: Additional information is available at the end of the chapter http://dx.doi.org/10.5772/52141 IntroductionVirgin olive oil (VOO) is obtained exclusively by mechanical extraction from the olive fruit and can be consumed crude without any further physical-chemical treatments of refining. Its sensory and health properties are intimately linked to its chemical characteristics, in particular to several minor components, which are strongly affected by the operative conditions of oil processing and can thus be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 52 publications
(91 reference statements)
5
19
0
Order By: Relevance
“…In fact, it was demonstrated that the 2-phases decanter preserves more of the phenolic compounds in comparison to the 3-phases decanter where the added water causes large amounts of phenols to be eliminated with the olive mill waste water [42] (12,16). Moreover, the high amount of O 2 dissolved in the pastes during the process of press and sinolea systems due to contact with the air result in a loss of phenolic compounds due to the activation of endogenous enzymes, polyphenoloxidase and peroxidase, that oxidize the phenolic compounds and consequently reduce their concentration in the produced oil [14].…”
Section: Total Phenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it was demonstrated that the 2-phases decanter preserves more of the phenolic compounds in comparison to the 3-phases decanter where the added water causes large amounts of phenols to be eliminated with the olive mill waste water [42] (12,16). Moreover, the high amount of O 2 dissolved in the pastes during the process of press and sinolea systems due to contact with the air result in a loss of phenolic compounds due to the activation of endogenous enzymes, polyphenoloxidase and peroxidase, that oxidize the phenolic compounds and consequently reduce their concentration in the produced oil [14].…”
Section: Total Phenolsmentioning
confidence: 99%
“…The selection of the processing systems could have a significant effect on the oil oxidation due to the exposure to air oxygen in the press and sinolea systems and the use of mats in the press system. These inconveniences in the aforementioned systems were completely overcome in the modern systems including the 2-and 3-phases [14,15]. However, the 3-phases system might result in a decrease in the phenolic and aromatic compounds leading to lower oxidative stability due to the use of water that could dissolve the hydrophilic phenols that will be removed with the olive mill waste water [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PPO seems to be the most relevant enzyme involved in phenolic oxidation in the milling process, while POD enzymes are mainly active in the malaxation process [17]. Therefore, the study of the influence of enzymatic activity on EVOO phenolic compounds profile changes is a current research challenge [18,19] since EVOO processing should include, as a main objective, the improvement of sensory and nutritional properties [20].…”
Section: Introductionmentioning
confidence: 99%
“…Every crusher exerting different mechanical action to break down the olive tissue elicits several effects due to variation induced in the olive paste, in terms of temperature, granulometry of fragments, and exposure to atmospheric oxygen. These variations play a crucial role for endogenous enzymatic activities, affecting the final amount of the EVOO as well as its phenolic and volatile profile [27,28]. During this phase, in fact, the entire heritage of olive fruit endogenous enzymes (cellulases, hemicellulases, pectinases, polygalacturonases, lipase, β-glucosidase, polyphenoloxidase (PPO), peroxidase (POD), and lipoxygenase (LOX)) is activated and involved in the subsequent phases of the extraction process and the formation and transformation of phenolic and volatile compounds in EVOO [29,30].…”
Section: Crushing Impact On Minor Components Of Evoomentioning
confidence: 99%
“…Several studies carried out on the distribution of olive fruit endogenous enzymes in its constitutive parts (pulp, stone and seed) have shown that the seed is particularly rich in POD, while the phenolic compounds are most concentrated in the pulp [28,32]. In particular, in olive pastes and the produced oil the decrease of phenols is due to their oxidation catalyzed by the POD and the PPO together.…”
Section: Crushing Impact On Minor Components Of Evoomentioning
confidence: 99%